Innovation via global route: Proposing a reference model for chances and challenges of global innovation processes - Rajnish Tiwari; Stephan Buse; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2007)
Innovations have acquired a key-role in the growth and competition strategies of firms today. They are regarded as an essential tool to stimulate growth and enable firms to master the competition brought about by the forces of globalization. In developed countries they are thought to provide a vital buffer against challenges from low-cost producers from emerging countries. At the same time, innovations in today's globalized world are hardly feasible in isolation. World-wide economic reforms and far-reaching technological advancements have brought to fore new economic powerhouses, such as China and India, which possess strong scientific capabilities. Products are marketed internationally which often necessitates adaptation to specific needs of targeted markets. All these developments are leading to the globalization of innovation. Based on recent empirical studies conducted by the authors in Germany, this paper presents results from research-in-progress and proposes a reference model for chances and challenges of global innovation activities.
urn:nbn:de:gbv:830-tubdok-3549
Keywords: 650; Research and Development; R&D; Internationalization; Globalization; Innovation